Interday and intraday stance analysis variability in dogs with hindlimb lameness and comparison of the effect of dog, surgeon, and TPLO surgical procedure variables on improvement of eight-week post-operative static weight-bearing. - Wilson, Megan L. (Kansas State University, 2018)
Interday and intraday stance analysis variability in dogs with hindlimb lameness Objective: The purpose of this study was to assess the same day and next-day repeatability of data collected with a Pet Safe Stance Analyzer on animals with naturally-occurring lameness presented for veterinary orthopedic examination. Our hypothesis was that dogs would show consistent repeatability with regards to body weight distribution on the Pet Safe Stance analyzer. Materials and Methods: Interday Variability Trial: Thirty-one consecutive dogs presenting for hindlimb lameness were included. The PetSafe Stance Analyzer was used with the dog standing in their natural standing position with each foot placed in its respective quadrant on the Stance Analyzer. A minimum of 5 valid measurements were collected and averaged to find the mean distribution of weight on each limb. This process was repeated the following day with the same handler and recorder. Intraday Variability Trial: Fifteen consecutive dogs were placed on the Pet Safe Stance analyzer and measurements were collected for each of 5 trials identical to the interday group. Four additional assessment trials followed with reintroduction of the animal to the room at each assessment. Results: Interday Variability Trial: There were no significant differences between Day 1 and Day 2 measured variables except for a significant increase in the Forelimb Symmetry index on Day 2 compared to Day 1. Lin’s Correlation Coefficients % body weight measured on Day 1 compared to Day 2 were significantly correlated on the lame hindlimb (0.524) and contralateral hindlimb (0.733). Intraday Variability Trial: There were no significant differences across trials for measured variables of % weight on the lame hindlimb, contralateral hindlimb, ipsilateral forelimb, or contralateral forelimb. Lin’s Correlation coefficients showed strong correlation between trials for the lame hindlimb (0.682), contralateral hindlimb (0.817), body weight (0.863), and hindlimb symmetry index (0.726). Clinical Significance: A commercial stance analyzer is a repeatable method of measurement of weight-bearing on lame hindlimbs of dogs between days and in repeated trials over one day. Day-to-day forelimb weight-bearing in dogs who are lame on a hindlimb is more variable, likely because of trial to trial changes in weight redistribution from lameness. Comparison of the effect of dog, surgeon, and TPLO surgical procedure variables on improvement of eight-week post-operative static weight-bearing Objective: To compare the effect of surgeon and tibial plateau leveling osteotomy (TPLO) procedure variations on the outcome of TPLO in naturally-occurring cranial cruciate-deficient stifles. Materials and methods: Records from 142 dogs receiving a TPLO were reviewed for information regarding surgical procedure, status of meniscus at the time of surgery, surgeon identity, ACVS diplomate or resident, meniscal release, progression of healing at the progress evaluation based on radiographic interpretation, and complications encountered. The primary outcome measure was static force on the operated limb at recheck on a PetSafe Stance Analyzer ͣ. Results: Recheck tibial plateau angle (TPA) was negatively and significantly correlated with improvement (r=-0.2132, p=0.013). Post-operative, and Recheck TPA’s were all significantly correlated with one another. The amount of TPA change from initial to immediate post-operative values was significantly correlated with the Initial TPA (r=0.628, p<0.001). Surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, post-operative TPA, and initial TPA had no significant effect on weight-bearing at recheck. Clinical Significance: TPLO’s show improvement of 4.58% BW on the operated limb at 6-12 week rechecks on a stance analyzer. Surgeon, surgical experience, arthrotomy, meniscal damage, meniscal intervention, complications, post-operative TPA, and initial TPA have no effect on surgical outcome.
Keywords: Stance Analysis; Tibial Plateau Leveling Osteotomy